The Effectiveness of Tax Administration Digitalization to Reduce Compliance Cost Taxpayers of Micro Small, and Medium Enterprises - Erin Erin (Budapest International Research and Critics University, 2021)
At this time, digitizing tax administration is one of the activities that can be an answer and development. The reason is that digitalization affects the role of the digital economy so that each country improves services, especially in tax administration. Indonesia is digitizing tax administration by implementing several technologies, especially in reducing taxpayer compliance costs for MSMEs. It is known that the number of SMEs in Indonesia continues to grow from 2015 to 2021, reaching 59 million business actors, so there is a need for more roles from the government to continue to improve taxpayer compliance for MSMEs. This research method uses qualitative descriptive and explanative. The data used is primary data collected through observation and survey distribution to SMEs. The results of this study show that knowledge, mediation, and tax satisfaction/perceived tax fairness variables affect the level of MSME taxpayer compliance in digitizing tax administration. Then, MSME taxpayers in meeting tax compliance costs, such as in tax services, the tax system is still not efficient and effective, as well as tax rates and sanctions that still tend to be burdensome for MSME taxpayers.